2021
DOI: 10.3389/fpubh.2021.683712
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions and Experiences of Mobile Health Technology by Older People in Guangzhou, China: A Qualitative Study

Abstract: The study explores older people's perceptions and experiences with mobile technology adoption in hospitals. Twenty nine older people were interviewed at a tertiary hospital in Guangzhou from June to December 2020. All the interviews were analyzed using thematic analysis. Older people are a diversified group. Various factors impact their readiness for technology use, including their educational level, age, past experiences, living arrangements, etc. The older people in this study in general expressed a great co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
(37 reference statements)
0
11
1
Order By: Relevance
“…Our study has further implications concerning the relationship between instrumental app use and the loneliness of OAs. Although Tu et al's (2021) study of Chinese OAs found involuntary use of mHealth apps was associated with negative wellbeing of OAs [45], we did not find any significant relationship between instrumental app use and loneliness. This was expected considering Hong Kong's OAs could largely use mobile apps based on personal willingness.…”
Section: Relationship Between Mobile App Use and Loneliness Of Hong K...contrasting
confidence: 99%
See 1 more Smart Citation
“…Our study has further implications concerning the relationship between instrumental app use and the loneliness of OAs. Although Tu et al's (2021) study of Chinese OAs found involuntary use of mHealth apps was associated with negative wellbeing of OAs [45], we did not find any significant relationship between instrumental app use and loneliness. This was expected considering Hong Kong's OAs could largely use mobile apps based on personal willingness.…”
Section: Relationship Between Mobile App Use and Loneliness Of Hong K...contrasting
confidence: 99%
“…An empirical study in China suggested that OAs felt frustrated and stressed after using mHealth apps. They had insufficient tech self-confidence and were unfamiliar with digitized procedures for making medical appointments [45]. Elsewhere, a further study indicated that involuntary and passive mobile app use could lead to decreased wellbeing among OAs [27].…”
Section: Selective Optimization With Compensation (Soc) Relationships...mentioning
confidence: 99%
“…However, the shortcomings of digital devices such as technological components, complicated operation interfaces and difficult understanding have further deepened the “digital divide,” resulting in the refusal of the elderly to wisdom healthcare service ( 12 , 13 ). Therefore, the elderly generally have low participation, recognition, and satisfaction with the wisdom healthcare model, which is not conducive to the further development and optimization of it, as well as to the expansion of academic research in this field ( 14 , 15 ). With that in mind, in the internet era with the rapid development of digital information, in order to further promote the development and optimization of the wisdom healthcare model and improve the quality of life of the elderly, this study, from the value perspective of wisdom healthcare, discusses the influence of the “digital divide for the elderly” on the value perception and satisfaction of wisdom healthcare, which has crucial theoretical and practical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Health-care scholars have identified a significant number of studies on the use of health technologies by different demographic groups, especially older people (Berauk et al , 2018; Klimova, 2016). Tu et al (2021) found that older people expressed great concern about using new health technologies because of the technological barriers they encountered. While health applications are potentially convenient for older people, scientific evidence of their popularity among younger generations is scarce (Lee, 2021; Schuuring et al , 2016).…”
Section: Introductionmentioning
confidence: 99%